Socialization of Increasing Student Participation to Continue Vocational Higher Education through the Socialization of the Sharia Finance and Banking Study Program - Dina Arfianti Siregar; Marlya Fatira AK; Sri Mulyono; Yuyu Rahayu; Mardelia Desfrida; Dias Putra Prayogi (ALTSA Publisher, 2024)
Socialization of increasing student participation to continue vocational higher education through the socialization of the Sharia Finance and Banking Study Program at Jl. Rambong Sialang No.50, Firdaus, Sei Rampah District, Serdang Bedagai Regency, North Sumatra 2099, aims to attract students to continue their education at the university level, especially at the Politeknik Negeri Medan and the Sharia Finance and Banking Study Program. Collecting data through descriptive and qualitative data is then analyzed and processed to produce solutions to the problems faced by partners. The data collection technique was conducted by interviewing the Principal of SMA Negeri 1 Sei Rampah. Data analysis techniques through descriptive analysis. The results of this report state that this socialization provides an introduction through socialization activities regarding the Introduction of the Sharia Finance and Banking Study Program of the Politeknik Negeri Medan. Providing understanding through socialization activities regarding the importance of education in higher education, especially at the Politeknik Negeri Medan